The Effectiveness of Punishment Sanctions for Narcotics Crime in Gresik District - Moh Rifki Dwi Galih Widodo (Jurnal Justiciabelen, 2024)
Drug abuse is a crime and a violation of the law. In modern times, the spread of drug abuse is increasing and the sale of illegal drugs is increasingly widespread from all walks of life. This resulted in a very detrimental impact and many victims were affected by drug abuse. Various government efforts to eradicate drug abuse and provide criminal sanctions against drug offenders. This study aims to determine the development of drug abuse cases, especially in Gresik Regency. And the effectiveness of giving sanctions to the perpetrators of drug abuse crimes.